Zakaj potrebujemo trajno rešitev za nabavo zdravil mimo postopkov po Zakonu o javnem naročanju (ZJN-3) - Rakovec, Romana (Pravnik, 2024)
Until 30 August 2024 this year, amendments and additions to the Slovenian Act on Pharmacy Activity (ZLD) were open for public consultation. The Chamber of Pharmacists of Slovenia (LZS), along with the majority of those involved in the supply of medicines to the population, welcomes most of the proposed changes. These amendments are the result of several years of efforts to ensure an uninterrupted supply of high-quality medicines, to reduce challenges in organising a continuous supply of medicines, and to improve the availability of medicines and pharmacy services for users. Given the general shortage of medicines and the small size of the Slovenian market, it is particularly important to highlight the proposed Article 14a of the amendment to the ZLD, which would permanently remove the obligation of public pharmacy institutes to purchase medicines (and other goods intended for resale) pursuant to Public Procurement Act (ZJN-3). The proposed amendments to the ZLD by the Ministry of Health confirm that the procurement of medicines in public pharmacy institutions must be appropriately regulated. This aligns with the fundamental purpose of pharmacy activity: to provide patients with high-quality medicines and ensure that each patient receives the correct medicine on time.
Keywords: javno naročanje; lekarna; lekarniška dejavnost; medicines; ministrstvo za zdravje; Ministry of Health; nabava zdravil; pharmacy; pharmacy activity; public procurement; Zakon o javnem naročanju; zdravila